Multiscale characterization of shellfish purple and other organic colorants in 20th-century traditional enredos from Oaxaca, Mexico. (October 2022) - Vermeulen, Marc; Tamburini, Diego; McGeachy, Alicia C.; Meyers, Rebecca D.; Walton, Marc S.
Abstract: Enredos are iconic textiles that have been produced for centuries by Mexican communities to celebrate pregnancy, weddings, etc. They have been traditionally dyed with three natural dyes, namely indigo, cochineal, and shellfish purple. In this study two modern enredos produced in the 1980s, now in the collection of the National Museum of Mexican Art, were investigated with the aim of understanding the colorants used and informing on the use of traditional dyeing practices in modern Oaxaca. The results were obtained by a combination of non-invasive analytical techniques, namely reflectance imaging spectroscopy (RIS) and macro X-ray fluorescence (MA-XRF), and high pressure liquid chromatography coupled to diode array detector and tandem mass spectrometry (HPLC-DAD-MS/MS). In addition to representing the first example of this combination of techniques applied to the study of textiles, this study also reports on the first characterization of the purple dye extracted from the Plicopurpura pansa G. mollusk by HPLC-DAD-MS/MS. Moreover, this study reveals the simultaneous use of synthetic red dyes with naturally-derived colorants such as indigo and shellfish purple. The limitations of the various techniques to provide an ultimate identification of certain dyes are emphasized together with the need for additional foundational research to expand molecular databases for the identification of synthetic dyes. Nevertheless, the results shed light on a dynamic dyeing scenario in modern Oaxaca (Mexico), in which traditional materials and methods are used alongside new ones in an attempt to preserve meaningful local practices. Highlights: Multimodal analysis of modern textiles form Oaxaca, Mexico. Characterization of shellfish purple and other colorants using MA-XRF, reflectance spectroscopy imaging and HPLC-DAD-MS/MS. Preservation of meaningful local practices through the use of traditional materials and methods alongside modern ones.